Editor’s Foreword (Vadim Radaev) - Vadim Radaev (Journal of Economic Sociology, 2022)
Dear colleagues, This issue of the Journal of Economic Sociology is published on the day of the 30th anniversary of the Higher School of Economics (HSE University). It may not be the best time for celebrations. However, we would not like to miss this important date. Our sincere congratulations to all our colleagues who worked at the HSE in previous years and stay with the HSE at present! Now we proceed to a new issue of our journal.